Strategi Pemberdayaan Masyarakat Dalam Meningkatkan Hasil Sektor Pertanian di Desa Suelain, Kecamatan Lobalain, Kabupaten Rote Ndao - Ndun, Gerivan; Jeni J. Therik; Aspri Budi Oktavianto (Universitas 17 Agustus 1945 Semarang, 2025)
This research aims to understand and analyze community empowerment strategies in improving agricultural sector outcomes in Suelain Village, Lobalain District, Rote Ndao Regency. The method used is a qualitative approach with descriptive research type. Data were collected through interviews, observations, and documentation. The results show that empowerment strategies are implemented through three main approaches: enabling (community empowerment as access), enhancing (community empowerment as capacity building), and protecting (community empowerment through protection). Although the strategies have been designed in an integrated manner, the implementation still faces various obstacles such as budget limitations, lack of technical training, and the suboptimal role of agricultural extension workers. This study recommends the need for efforts to strengthen institutions and enhance collaboration among stakeholders to support the success of farmer community empowerment.